Uma proposta de ensino-aprendizagem para produção de textos de divulgação científica em cursos de licenciatura - Lopes, Jonatas Brasil (Brasil, 2023)
The recent waves of Covid-19 accompanied by a veritable avalanche of fake news about the disease, the virus, and vaccines, have increased the concern about bringing the common citizen closer to scientific thinking. Much has been debated about the dissemination of new scientific knowledge and the distance between science and society in general. Considering the existence of few materials of Scientific Dissemination (SD) in the Amazonian context, there is a need for actions that promote the teaching of SD starting in undergraduate courses. This research was concerned with helping future teachers to produce Scientific Dissemination Texts (SDT) strengthening the access to scientific topics with accessible language. Therefore, a case study was carried out, with the main objective of evaluating a teaching-learning proposal for the construction of SDT. This was implemented through a workshop called "Building SDT", with the use of planned learning scripts based on Constructive Alignment in order to stimulate autonomous study. The content was based on the parameters of analysis and construction of the SDT and the form of evaluation was done by means of rubrics developed for this purpose. The subjects of this investigation were students of the Degree Course in Biological Sciences of the Federal Institute of Education, Science and Technology of Amazonas (IFAM - Campus Manaus Centro). In the proposal, it was sought to develop some skills that the disseminator of scientific knowledge should appropriate with regard to the design and structure of this type of text. As results, through various instruments of data collection, were pointed out: gaps in the understanding of the students about the composition and organization of a SDT, as well as the elements and the search for the scientific article; the aid of initial resources in the composition of a text directing the planning of writing; the expansion and improvement of the perception of the composition and structure of a SDT through access to the parameters and rubrics provided by the application of the workshop; the suggestion of inclusion of the teaching-learning proposal in teacher training in undergraduate courses. After the evaluation and the necessary adjustments, an Educational Product named "Introductory Course for the construction of a Scientific Dissemination Text: a didactic guide for teachers" was organized, containing guidelines for: (a) knowing the theoretical basis that guided the teaching-learning proposal (b) helping in the planning and implementation of the proposal (c) building a SDT following the steps of the proposal.